Distinct trajectories of HbA1c in newly diagnosed Type 2 diabetes from the DPV registry using a longitudinal group‐based modelling approach. Issue 11 (23rd September 2019) - Rathmann, W.; Schwandt, A.; Hermann, J. M.; Kuss, O.; Roden, M.; Laubner, K.; Best, F.; Ebner, S.; Plaumann, M.; Holl, R. W.
Abstract: Aim: To identify groups of heterogeneous HbA1c trajectories over time in newly diagnosed Type 2 diabetes. Methods: The study comprised 6355 adults with newly diagnosed Type 2 diabetes (55% men, median age 62 years, baseline BMI 31 kg/m 2 ) from the Diabetes Patienten Verlaufsdokumentation ( DPV ) prospective multicentre diabetes registry (Germany, Austria). Individuals were assessed during the first 5 years after diabetes diagnosis if they had ≥ 3 aggregated HbA1c measurements during follow‐up. Latent class growth modelling was used to determine distinct subgroups that followed similar longitudinal HbA1c patterns (SAS: Proc Traj). Multinomial logistic regression models were used to investigate which variables were associated with the respective HbA1c trajectory groups. Results: Four distinct longitudinal HbA1c trajectory (glycaemic control) groups were found. The largest group (56% of participants) maintained stable good glycaemic control (HbA1c 42–45 mmol/mol). Twenty‐six percent maintained stable moderate glycaemic control (HbA1c 57–62 mmol/mol). A third group (12%) initially showed severe hyperglycaemia (HbA1c 97 mmol/mol) but reached good glycaemic control within 1 year. The smallest group (6%) showed stable poor glycaemic control (HbA1c 79–88 mmol/mol). Younger age at diabetes diagnosis, male sex, and higher BMI were associated with the stable moderate or poor glycaemic control groups. Insulin therapy was strongly associated with the highly improved glycaemic control group. Conclusions: Four subgroups with distinct HbA1c trajectories were determined in newly diagnosed Type 2 diabetes using a group‐based modelling approach. Approximately one‐third of people with newly diagnosed Type 2 diabetes need either better medication adherence or earlier intensification of glucose‐lowering therapy. What's new?: Currently, data on HbA1c trajectories in newly diagnosed Type 2 diabetes are limited. This longitudinal study identified four distinct HbA1c trajectories during the first 5 years after Type 2 diabetes diagnosis. The largest group (56%) showed persistent good glycaemic control, whereas two smaller groups exhibited either stable moderate (26%) or poor (6%) glycaemic control, respectively. Twelve percent of people with Type 2 diabetes showed initial poor glycaemic control, which highly improved during the first year after diabetes diagnosis. A personalized medicine approach in the treatment of newly diagnosed Type 2 diabetes could be supported by identification of subgroups with specific HbA1c trajectories in response to glucose‐lowering therapy.